Development of Augmented Reality (AR) Based Learning Media to Improve Educational Outcomes for Elementary School Students - Nurachmadani, Nadila; Sahudra, Tengku Muhammad; Mulyahati, Bunga (LPPPI Publishing, 2025)
This research focuses on creating a learning media product that utilizes Augmented Reality (AR) for teaching IPAS, particularly aimed at fifth-grade students in Social Studies. The study was conducted to evaluate the validation from experts in media, subject matter, and student testing, as well as to assess the practicality and effectiveness of student learning outcomes after engaging with the AR-based learning media. Utilizing a Research and Development (R&D) methodology, this study follows the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used include observation, interviews, documentation, and validation questionnaires for experts, as well as response questionnaires for teachers and students.The validation results from media experts showed a percentage of 97.14% with a